MENGEMBANGKAN FITRAH ANAK MELALUI PENDIDIKAN ISLAM (Studi atas Pemikiran Hamka) - Mohamad Salik (lp2m-uin malang, 2014)
Oleh: Mohamad Salik UIN Sunan Ampel Surabaya Email: salik_mohamad@yahoo.com Abstract Hamka was one of Muslim intellectuals who played a significant role in modernization of Islamic education. Among of his thoughts are: According to Hamka, Developing human fitrah is the main purpose of Islamic education. In this way, he emphasizes the important of moral education and the need of developing intellect in teaching learning process. There are some principles that must be considered to achieve this goal: a) The curriculum must be able to develop social-emotion and lead students to be more obedient to God. b) The approach used must be able to encourage students to implement their knowledge and actualize their belief and obedience in their daily life. b) The method must be able to encourage students to have critical minded. In this way, parents and teachers need to give room of freedom for the students to think and determine their own way of life based on their fitrah and talents. To achieve this goal,the involvement teachers, parents, and society are absolutely important. Hamka was not only the thinker of Islamic education, but also directly involved in establishing and developing education institutions. Among of them were Tabligh School in Minangkabau and Islamic Education Institution Al-Azhar Jakarta.